Supramolecular reagents for the construction of predictable architectures - Smith, Michelle M. (Kansas State University, 2008)
Tailoring the properties of a bulk material such as a pharmaceutical compound, through non-covalent interactions, could lead to the enhancement of its physical properties without chemically modifying the individual molecules themselves. In order to obtain a degree of control and reliability of these non-covalent interactions, we must develop a series of synthons - patterns of non-covalent interactions between molecules. A family a N-heterocyclic amides were synthesised and an assessment of their binding selectivities was made, by evaluation of the supramolecular yield, (the frequency of occurrence of the desired connectivities). It was found that the supramolecular yield increased with increasing basicity of the heterocyclic nitrogen atom. However, there is a point where the heterocycle becomes basic enough to produce salts, which often leads to unpredictable connectivity and stoichiometry. Once the effectiveness of the N-heterocyclic amides as supramolecular reagents was established, a series of more closely-related ditopic hydrogen-bond acceptor molecules were synthesized. The supramolecular reagents contained imidazole and pyridine binding sites, so that the two sites differ in terms of their basicity and geometry. An assessment of the ability of these molecules to induce selectivity when a hydrogen bond donor such as a cyanoxime or a carboxylic acid is introduced was made. A total of nineteen crystal structures were obtained, of which one yielded a salt with unpredictable connectivity, and eighteen were cocrystals. Ten of these were 2:1 co-crystals, which shows that the two sites are accessible for binding. Eight were 1:1 stoichiometry, with five out of eight (63%) forming a hydrogen bond to the best acceptor. In addition, a series of molecular electrostatic potential calculations were employed to investigate the binding preferences and probe the best donor/best acceptor hypothesis. A ternary supermolecule was also constructed from a central, asymmetric hydrogen-bond acceptor and two different hydrogen-bond donor molecules. It was found that the best donor, the cyanoxime, bound to the best acceptor, the imidazole nitrogen atom, while the second best donor, a carboxylic acid, bound to the second best acceptor. The calculated molecular electrostatic potential values were used to rationalize this event. A series of substituted cyanophenyloxime, hydrogen bond donor molecules were synthesized and their effectiveness at forming co-crystals was examined. It was found that simple R group substitution could have a significant effect upon the co-crystal forming ability of the hydrogen bond donors, having improved the yield from 4% and 7% in a series of co-crystallizations with closely-related oximes, to 96% with the cyanoximes. A series of di- and tritopic cyanoximes were synthesized and an assessment of their co-crystal-forming ability was made. They were found to be equally effective at producing co-crystals as the monotopic cyanoximes, having done so in 23 out of 24 cases. In contrast to their carboxylic acid counterparts, the polycyanoximes also exhibited excellent solubility. Finally, a series of ditopic ligands (N-heterocyclic amide and pyridyl cyanoximes) were employed in the synthesis of metal complexes. The amide-based ligands were found to be very effective at organizing the metal architectures with coordination through the heterocyclic nitrogen atom and propagation of one-dimensional chains through carboxamidecarboxamide interactions. These interactions prevailed even in the presence of potentially disruptive species such as solvent molecules, (in Ag(I) complexes) counterions, or other hydrogen bond acceptors. The self-complementarity of the oxime moiety was found not to prevail in any of the cases, but the pyridyl cyanoximes were consistent in their behaviour, forming an O-H…O (oxime-oxygen) hydrogen bond to a carboxylate or acac moiety.
Keywords: Supramolecular; Crystal Engineering; Co-crystallization; Non-covalent Synthesis; Chemistry, Inorganic (0488)